Impact of the novel coronavirus disease on treatment adherence and sleep duration in patients with obstructive sleep apnea treated with positive airway pressure - Batool-Anwar, Salma (J Clin Sleep Med, 2020)
STUDY OBJECTIVES: The study objective was to examine the effect of coronavirus disease on treatment adherence and self-reported sleep duration among patients with obstructive sleep apnea (OSA) treated with positive airway pressure therapy. METHODS: This was a retrospective review of medical records of patients seen in the Sleep and Circadian Clinic at Brigham Health during the immediate period of 1 month after the national lockdown was announced on March 15, 2020. Patients with OSA were included only if positive airway pressure adherence data were available in the 12 months before and in the month after the lockdown. Patients with other sleep disorders and patients with OSA without adherence data were excluded. RESULTS: The mean age of the patients was 63.5 ± 13.9 years, 55% of the participants were men, and the mean body mass index was 31.8 ± 7.9 kg/m(2). Severe OSA was noted among 59.5% compared with 29.3% with moderate OSA, and 11.2% with mild OSA. An increased number of patients reported insomnia after the lockdown (41% vs 48%, P = .02). Sex stratification showed worsening insomnia only among women. There was no significant difference in positive airway pressure adherence as measured by hours of use, self-reported sleep duration, or use of sleep medications. CONCLUSIONS: Post– coronavirus disease lockdown had a negative impact on sleep as evidenced by increased reporting of insomnia, particularly among women, but no impact on positive airway pressure adherence or self-reported sleep duration. CITATION: Batool-Anwar S, Omobomi OS, Quan SF. Impact of the novel coronavirus disease on treatment adherence and sleep duration in patients with obstructive sleep apnea treated with positive airway pressure. J Clin Sleep Med. 2020;16(11): 1917–1920.